Influence of Ceramic Roof Tile Waste Powder as A Cementitious Material on The Slump Flow Of Mortar - Voilla Oktaviani; Agus Maryoto; Nor Intang Setyo Hermanto (Engineering Faculty, UNSOED, 2026)
The increasing demand for sustainable construction materials has encouraged the utilization of ceramic waste as a supplementary cementitious material due to its potential to reduce environmental impacts and improve resource efficiency. Ceramic roof tiles are manufactured from clay obtained mining activities, which can alter natural land topography. The annual production of ceramic roof tiles in Kebumen Regency is estimated at 174,424,333 units, with approximately 95% as standard quality requirements, resulting an estimated waste generation about 8,721,216 units per year. Therefore, this study aims to investigate the effect of ceramic roof tile waste powder (CRTWP) as a cement substitution material on the workability of mortar. The novelty of this study lies in investigating the influence of CRTWP with a fineness higher than cement on mortar slump flow behavior. The experimental program included fineness testing using a Blaine apparatus and slump flow testing using a flow table. CRTWP was used in varying percentages: 0%, 10%, 20% 30%, and 100%. The results indicate that increasing the proportion of CRTWP in the mortar mixture leads to a reduction in slump flow, thereby decreasing the workability of the mortar.